Bibliometric Indicators in Nanoscience - Masatsura Igami (Foresight and STI Governance, 2008)
This document presents a new bibliometric method that enables us to comprehend and track the changing nature of scientific activities. Special emphasis is put on understanding how nanoscience is evolving across disciplines and across countries and regions. The analysis addresses questions like: How are scientific areas in nanoscience linked to each others? How can the multidisciplinary character of nanoscience be assessed? Which countries play a prominent role in nanoscience? How can international knowledge flows be measured?